Transepithelial transport across the blood–testis barrier. Issue 6 (December 2018) - Miller, Siennah R; Cherrington, Nathan J
Abstract : The blood–testis barrier protects developing germ cells by limiting the entry of xenobiotics into the adluminal compartment. There is strong evidence that the male genital tract can serve as a sanctuary site, an area of the body where tumors or viruses are able to survive treatments because most drugs are unable to reach therapeutic concentrations. Recent work has classified the expression and localization of endogenous transporters in the male genital tract as well as the discovery of a transepithelial transport pathway as the molecular mechanism by which nucleoside analogs may be able to circumvent the blood–testis barrier. Designing drug therapies that utilize transepithelial transport pathways may improve drug disposition to this sanctuary site. Strategies that improve disposition into the male genital tract could reduce the rate of testicular relapse, decrease viral load in semen, and improve therapeutic strategies for male fertility.